2008
DOI: 10.1128/aem.01835-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of “ Dehalococcoides ethenogenes ” 195 and an Enrichment Culture Containing Unsequenced “ Dehalococcoides ” Strains

Abstract: Tetrachloroethene (PCE) and trichloroethene (TCE) are prevalent groundwater contaminants that can be completely reductively dehalogenated by some "Dehalococcoides" organisms. A Dehalococcoides-organism-containing microbial consortium (referred to as ANAS) with the ability to degrade TCE to ethene, an innocuous end product, was previously enriched from contaminated soil. A whole-genome photolithographic microarray was developed based on the genome of "Dehalococcoides ethenogenes" 195. This microarray contains p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 36 publications
3
59
0
Order By: Relevance
“…The dceA7 gene (100% identity to DET0088) is truncated, and the 3 0 anchoring protein is replaced by a hypothetical protein. Nevertheless, recent studies have reported that the expression of DET0088 was upregulated during PCE dechlorination in Alameda Naval Air Station enrichments and mixed cultures containing strain 195 (Rahm et al, 2006;West et al, 2008). Also, the dceA7 gene was identified using the newly designed primer pairs, RDH F1C and RDH R1C, revealing inadequacies of the previous degenerate primer pair.…”
Section: Discussionmentioning
confidence: 99%
“…The dceA7 gene (100% identity to DET0088) is truncated, and the 3 0 anchoring protein is replaced by a hypothetical protein. Nevertheless, recent studies have reported that the expression of DET0088 was upregulated during PCE dechlorination in Alameda Naval Air Station enrichments and mixed cultures containing strain 195 (Rahm et al, 2006;West et al, 2008). Also, the dceA7 gene was identified using the newly designed primer pairs, RDH F1C and RDH R1C, revealing inadequacies of the previous degenerate primer pair.…”
Section: Discussionmentioning
confidence: 99%
“…For metagenomic sequencing, samples from the same time point (27 h) from four different feeding cycles were pooled to collect enough material for sequencing. Total nucleic acids were extracted from frozen filters using a modified version of the bead beating and phenol extraction method described previously (West et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…This culture was derived from sediment collected at the Alameda Naval Air Station and is referred to as ANAS (Richardson et al, 2002). The phylogenetic composition of ANAS has been studied using clone libraries (Richardson et al, 2002;Lee et al, 2006), and the Dhc strains in ANAS have been analyzed using quantitative PCR and whole-genome microarrays West et al, 2008;Lee et al, 2011). ANAS contains two Dhc strains, which have recently been isolated Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several molecular tools have been developed for examining a broad range of rdhA genes in a given sample (site, isolate or mixed culture), including both microarray-based methods and PCR-based protocols [60][61][62][63]. Identification of novel reductive dehalogenase genes has primarily come from PCR studies [32,33,[35][36][37]39,40,42] and subsequently from genome and metagenome sequencing efforts [6,13,14,41,63], with each new organism or environment sampled increasing the known diversity of putative rdhA genes.…”
Section: Reductive Dehalogenasesmentioning
confidence: 99%